Mechanisms of gastroprotective effects of ethanolic leaf extract of jasminum sambac against HCl/ethanol-induced gastric mucosal injury in rats - Abdulla, Mahmood Ameen; AlRashdi, A.S.; Salama, S.M.; Alkiyumi, S.S.; Hadi, A.H.A.; Abdelwahab, S.I.; Taha, M.M.; Hussiani, J.; Asykin, N. (Hindawi, 2012)
Jasminum sambac is used in folk medicine as the treatment of many diseases. The aim of the present investigation is to evaluate the gastroprotective effects of ethanolic extracts of J. sambac leaves against acidified ethanol-induced gastric ulcers in rats. Seven groups of rats were orally pre-treated with carboxymethylcellulose (CMC) as normal group, CMC as ulcer group, 20 mg/kg of omeprazole as positive group, 62.5, 125, 250, and 500 mg/kg of extract as the experimental groups, respectively. An hour later, CMC was given orally to normal group and acidified ethanol solution was given orally to the ulcer control, positive control, and the experimental groups. The rats were sacrificed after an hour later. Acidity of gastric content, the gastric wall mucus, ulcer areas, and histology and immunohistochemistry of the gastric wall were assessed. Gastric homogenates were determined for prostaglandin E2 (PGE2), superoxide dismutase (SOD), andmalondialdehyde (MDA) content. Ulcer group exhibited significantly severe mucosal injury as compared with omeprazole or extract which shows significant protection towards gastric mucosal injury the plant promotes ulcer protection as it shows significant reduction of ulcer area grossly, and histology showed marked reduction of edema and leucocytes infiltration of submucosal layer compared with ulcer group. Immunohistochemistry showed overexpression of Hsp70 protein and downexpression of Bax protein in rats pretreated with extract. Significant increased in the pH, mucus of gastric content and high levels of PGE2, SOD and reduced amount of MDA was observed.